Oxygen diffusion in superconducting oxides - Grandini, Carlos Roberto [UNESP]; de Albuquerque Gimenez, Juliana Maria [UNESP]; da Silva, Marcos Ribeiro [UNESP]; do Nascimento, Rodney Marcelo [UNESP] (Trans Tech Publications Ltd, 2008)
Since the discovery of high-temperature superconductivity of cuprate oxides, it has been clear that it is strongly affected by the oxygen content, which is also a crucial factor to determine other physical properties of high T-c superconductors. Non-stoichiometric (interstitial) oxygen strongly influences the physical properties of various superconducting oxides, in particular by creating conducting holes. It is now ascertained that the amount of holes injected depends not only on the content of interstitial oxygen, but also on its ordering. Rearrangement of the oxygen ordering may occur even below room temperature due to the unusual high mobility of these atoms. This way, mechanical spectroscopy is one of the most adequate techniques for the study of the mobility (diffusion) of oxygen atoms. This technique allows the determination of the jump frequency of an atomic species precisely, regardless of the model or the different possible types of jumps. In order to evaluate the mobility and the effect of oxygen content on these oxides, ceramic samples we prepared and submitted to several oxygen removal cycles alternately with mechanical relaxation measurements. As for SBCO, it was assumed that the peak was due to O(1)-O(5) jumps of oxygen atoms at the chain terminals or in chain fragments in the orthorhombic phase. In the case of BSCCO, the results showed complex anelastic relaxation structures, which were attributed to interstitial oxygen atom jumps between two adjacent CuO planes.
Keywords: diffusion; superconducting oxides; interstitial oxygen